Zakat Policy and Regulation: A Review - Aisyah As-Salafiyah; Ahlis Fatoni (SMART Insight, 2021)
This study reviews the Zakat policy in Scopus indexed journals. This analysis uses descriptive statistical analysis based on 92 selected papers related to the Zakat policy from national and international journals. All samples of published journals have been published until 2022. The export data is then processed and analyzed using the VOSviewer application program to find out the bibliometric visualization map to develop Zakat policy research. The results of this bibliometric mapping research show a map of the development of research in Zakat policy. The most popular keywords are zakat, poverty alleviation, and economic growth. The most famous author is Wahid H. The most popular institution is Accounting Research Institute (ARI). The most popular country is Malaysia. In addition, this study also finds several issues that are widely discussed in the literature regarding zakat policy in Indonesia.